Implementasi Pendekatan TARL dalam Pembelajaran Diferensiasi untuk Meningkatkan Pemahaman Konsep IPAS Siswa Kelas VI - Rosyidah, Aprilia Sabela; Ermawati, Diana; Khairunisa, Imada (MASALIQ, 2025)
This study aims to improve the conceptual understanding of Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial or IPAS) among sixth-grade students at SDN Demangan Kudus through the implementation of the Teaching at the Right Level (TaRL) approach within the context of differentiated instruction. The background of this research is the low level of conceptual understanding of IPAS and the gap in students’ initial abilities and basic literacy due to the use of a uniform instructional model. The method used was classroom action research based on the Kemmis and McTaggart model, with 15 students as subjects. Data collection techniques included interviews, observation, tests, and documentation. The results showed a gradual improvement in conceptual mastery of IPAS, increasing from 46.66% in the pre-cycle to 73.33% in the first cycle, and further to 80% in the second cycle. These findings indicate that the application of the TaRL approach in differentiated instruction effectively addresses students’ learning needs more accurately. The conclusion of this study is that instructional strategies tailored to students’ individual skill levels can significantly enhance conceptual understanding of IPAS at the elementary level and contribute to the development of more inclusive and adaptive learning models.